Synergie between molecular imprinted polymer based on solid-phase extraction and quartz crystal microbalance technique for 8-OHdG sensing - Ersöz, Arzu; Diltemiz, S. Emir; Özcan, A. Atılır; Denizli, Adil; Say, Rıdvan (Biosensors & bioelectronics, 2008)
Recently, the 8-hydroxy-2′-deoxyguanosine (8-OHdG) has been used as a marker to determine the oxidative stress. There is no any cheap and easy determination method based on chips and sensor systems for the determination of 8-OHdG. In this study, we have proposed imprinting methods for 8-OHdG recognition and determination using methacryloylamidohistidine-platinum(II) [MAH-Pt(II)] as a new metal-chelating monomer. The study includes the solid-phase extraction (SPE) of blood sample by a new 8-OHdG imprinted sorbent and the measurement of binding interaction of 8-OHdG imprinted quartz crystal microbalance (QCM) sensor via ligand interaction. 8-OHdG imprinted sorbent has prepared by bulk polymerization of MAH-Pt(II) and N- N′-methylenebisacrylamide. 8-OHdG imprinted sensor has prepared on a QCM chip coating the thiol pretreated Au electrode. At the end of these steps, a thin molecular imprinted polymer (MIP) film for the detection of 8-OHdG has developed and analytical performance of QCM sensor which has prepared using MIP was investigated. The affinity constant ( K a) for 8-OHdG using MAH-Pt-based thin film has determined by using the Scatchard method. The average percentage recovery of 8-OHdG from plasma samples was found as 80% by using of 8-OHdG imprinted SPE material. At the last step, 8-OHdG level in several blood plasma has been determined by this improved QCM sensor. The obtained results confirmed that the 8-OHdG level in cancer patient's blood was significantly higher than in general subjects.